Development, implementation, and validation of a generic nutrient recovery model (NRM) library. (January 2018) - Vaneeckhaute, C.; Claeys, F.H.A.; Tack, F.M.G.; Meers, E.; Belia, E.; Vanrolleghem, P.A.
Abstract: The reported research developed a generic nutrient recovery model (NRM) library based on detailed chemical solution speciation and reaction kinetics, with focus on fertilizer quality and quantity as model outputs. Dynamic physicochemical three-phase process models for precipitation/crystallization, stripping and acidic air scrubbing as key unit processes were developed. In addition, a compatible biological-physicochemical anaerobic digester model was built. The latter includes sulfurgenesis, biological N/P/K/S release/uptake, interactions with organics, among other relevant processes, such as precipitation, ion pairing and liquid-gas transfer. Using a systematic database reduction procedure, a 3- to 5-fold improvement of model simulation speeds was obtained as compared to using full standard thermodynamic databases. Missing components and reactions in existing standard databases were discovered. Hence, a generic nutrient recovery database was created for future applications. The models were verified and validated against a range of experimental results. Their functionality in terms of increased process understanding and optimization was demonstrated. Graphical abstract: Highlights: The first generic nutrient recovery model library was developed and implemented. An efficient numerical solution strategy was established through model coupling. Implementation correctness was verified using a 6-step procedure. Steady-state simulation results showed excellent agreement with experimental results. The models were applied as tool for increased process understanding & optimization.